2001
DOI: 10.1055/s-0037-1616110
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Phospholipids in Tissue Factor-initiated Thrombin Generation

Abstract: SummaryThe influence of platelets on tissue factor (TF)-initiated thrombin generation in a reconstituted model of blood coagulation and in whole blood was evaluated. No thrombin generation was observed over 15 min in the reconstituted model when either TF or platelets and phospholipids were omitted. At 25 pM TF, the rates of thrombin generation were platelet and PCPS concentration-dependent and achieved maximum (1.0 nM/s) in the physiological range of platelet concentration. Similar rates were achieved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 49 publications
9
77
0
Order By: Relevance
“…Figure 1A (f) shows thrombin generation in the presence of 2 M PCPS (1-2 M PCPS is equivalent to 2 ϫ 10 8 /mL platelets in supporting thrombin generation 50 ) initiated by 25 pM TF with factor VIIa at a physiologic concentration (0.1 nM). The initiation phase lasted approximately 3 minutes, and maximum levels of thrombin (ϳ 390 nM) were achieved 7 minutes after initiation of the reaction.…”
Section: Factor Viia and Tf In Normal Bloodmentioning
confidence: 80%
“…Figure 1A (f) shows thrombin generation in the presence of 2 M PCPS (1-2 M PCPS is equivalent to 2 ϫ 10 8 /mL platelets in supporting thrombin generation 50 ) initiated by 25 pM TF with factor VIIa at a physiologic concentration (0.1 nM). The initiation phase lasted approximately 3 minutes, and maximum levels of thrombin (ϳ 390 nM) were achieved 7 minutes after initiation of the reaction.…”
Section: Factor Viia and Tf In Normal Bloodmentioning
confidence: 80%
“…66 Similarly, reductions in platelet counts (Ͻ10 000/mm 3 ) elicit dependence on platelet concentration. 64 The end point used in evaluating hemostasis in most bioassays is the generation of a fibrin clot. As illustrated in Figure 4, the formation of a fibrin clot occurs at 10 to 30 nmol/L thrombin or Ϸ3% of the total amount of thrombin produced during the reaction, which is provided by only Ϸ7 pmol/L prothrombinase.…”
Section: Mann Et Al Dynamics Of Thrombin Formation 19mentioning
confidence: 99%
“…These have included the following: (1) synthetic plasma, in which mixtures prepared from purified procoagulants and anticoagulants and a natural or synthetic membrane source are induced to react by the addition of lipid reconstituted tissue factor 9,10,41,55-60 ; (2) paravivo studies of coagulation, in which whole, contact pathway-suppressed blood obtained by phlebotomy and maintained at 37°is induced to clot by addition of a fixed amount of membrane reconstituted tissue factor 42,[61][62][63][64][65][66][67][68] ; (3) numerical (computer) models of the coagulation system, which are based on the ensemble of published (and estimated) rate constants and concentrations of procoagulants and stoichiometric inhibitors and the mechanisms of their interactions 69 -71 (also referred to as "in silico" simulations); and (4) in vivo studies of the hemostatic reaction, in which whole blood exuding from a microvascular wound is sequentially sampled for relevant product formation. [72][73][74][75] Each of the model systems used has specific benefits and limitations.…”
Section: Models Of the Blood Coagulation Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies primarily utilize artificial phospholipid vesicles (PCPS) as a surrogate membrane surface to study the process of blood coagulation. It has been demonstrated that PCPS at 1 to 2 g.mol/L is equivalent to platelets at physiological concentrations (2 x 10 8 /mL) in supporting thrombin generation [25]. However, platelets (and phospholipid) at physiological concentrations do not saturate the reactions of blood coagulation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%